2011
DOI: 10.1111/j.1440-1746.2010.06509.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease's prevalence and impact on alanine aminotransferase associated with metabolic syndrome in the Chinese

Abstract: The prevalence of NAFLD has become epidemic in Shanghai adults. NAFLD combined with ALT levels may be used to identify the individuals at the different risk levels of metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
1
44
1
2
Order By: Relevance
“…The reported prevalence of NAFLD varies widely depending on the population studied and the definition used [14][15][16][17][18]. Age, gender, and ethnic differences are present in both the prevalence and severity of NAFLD/NASH [19][20][21].…”
Section: Epidemiologymentioning
confidence: 99%
“…The reported prevalence of NAFLD varies widely depending on the population studied and the definition used [14][15][16][17][18]. Age, gender, and ethnic differences are present in both the prevalence and severity of NAFLD/NASH [19][20][21].…”
Section: Epidemiologymentioning
confidence: 99%
“…156 Definite diagnosis of this lysosomal storage disease, which requires demonstration of a significantly deficient LAL activity followed by molecular sequencing of the LIPA gene, 157 has major clinical consequences given that enzyme replacement therapy with sebelipase alfa is safe and effective. 158,159 Based on studies showing that hypertriglyceridemia is the most common feature and is an independent predictor of NAFLD, [160][161][162][163][164] we recommend that hypertriglyceridemic should invariably undergo liver ultrasonagraphy. In particular, mixed hyperlipidemia associated with raised ALT accurately predicts NAFLD.…”
Section: Hyperlipidemia and Hypolipidemiamentioning
confidence: 99%
“…2 It is reported that NAFLD affects ≈30% of the general population in Western countries. 3 A recent epidemiological study revealed that in a Chinese population, the prevalence of NAFLD is 23.3%, 4 which indicates that not only in the Western population, but also in the relatively leaner Chinese population, NAFLD is highly epidemic.…”
mentioning
confidence: 99%